2010
DOI: 10.5251/abjna.2010.1.5.923.929
|View full text |Cite
|
Sign up to set email alerts
|

Herbage yield and chemical composition of four varieties of Napier (Pennisetum purpureum) grass harvested at three different days after planting

Abstract: An experiment was conducted to assess the herbage yield and chemical composition of 4 varieties of Napier grass (Pennisetum purpureum) harvested at 3 different days after planting. The varieties tested were obtained from ILRI (formerly ILCA) were Local, 16798, 16786 and 16840 and used in a 4x3 factorial arrangement of treatments with four replicate plots each. The herbage yield of the varieties were measured at 60, 90, 120 days after planting. The herbage of the varieties were harvested and separated into leaf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
32
4
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(54 citation statements)
references
References 4 publications
16
32
4
2
Order By: Relevance
“…Napier grass (Pennisetum purpureum), also known as Elephant grass, has been the most promising high-yielding fodder, giving DM yields that surpass most other tropical grasses (Ansah et al, 2010). It originates from sub-Saharan tropical Africa (Clayton et al, 2013) and has been introduced in most tropical and subtropical regions worldwide as forage.…”
Section: Introductionmentioning
confidence: 99%
“…Napier grass (Pennisetum purpureum), also known as Elephant grass, has been the most promising high-yielding fodder, giving DM yields that surpass most other tropical grasses (Ansah et al, 2010). It originates from sub-Saharan tropical Africa (Clayton et al, 2013) and has been introduced in most tropical and subtropical regions worldwide as forage.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies using ILRI accessions (Ansar et al, 2010;Tessema et al, 2010) showed that their biomass production is influenced by the environment and management, in addition to other traits inherent in the accessions.…”
Section: Dry Matter Yieldsmentioning
confidence: 99%
“…It is estimated that biomass harvested in the Northern Hemisphere from wood products has an energy content equal to 107% of the liquid fuel consumption of the United States (Goodale et al, 2002). Perennial plants such as switchgrass, Miscanthus and Napier grass have high photosynthetic capacity, as well as water and nitrogen use efficiency (Somerville et al, 2010;Ansah et al, 2010). They are fast growing and have efficient root systems allowing them to reach deep into the soil for water.…”
Section: Feedstocks and Conversion Technologiesmentioning
confidence: 99%